Parental Overprotective Behavior And Adjustment In Adolescent Girls - Utami, Narastri Insan; Alfatikah, Syifa (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to determine the relationship between parents' overprotective behavior and self-adjustment in adolescent girls. The hypothesis proposed in this study is that there is a negative relationship between parental overprotective behavior and self-adjustment in adolescent girls. The subjects in this study totaled 100 subjects, namely high school students. Data retrieval using the likert scale. The data analysis technique used is a product moment correlation test. The results of the correlation test for overprotective variables with self-adjustment in adolescent girls showed (rxy) = -0.697 with p = 0.000, meaning that the hypothesis that there is a correlation between overprotective behavior and self-adjustment is acceptable. Effective donation (R²) showed that overprotective behavior towards self-adjustment contributed 48% and the remaining 52% was influenced by other factors.